Biochemical, hematological and immunological effects of repeated propofol anaesthesia in dogs [Kopeklerde tekrarlanan propofol anestezisinin biyokimyasal, hematolojik ve immunolojik etkileri] - (:unkn) unknown (My University, 1997)
This study was designed to investigate biochemical, hematological and immunological effects of repeated propofol anesthesia in dogs. Histopathological examinations of liver and kidney tissue samples were also performed. Eight mongrel dogs were included in the study. Anaesthesia was induced with propofol in a dose of 3.5 mg/kg and maintained with 12 mg/kg/hr. Propofol anaesthesia was repeated for five times at weekly intervals. Blood samples were obtained for albumin, alkaline phosphatase, LDH5, ALT, AST, GGT, bilirubin, BUN, creatinine, cholesterol, triglycerides, HDL, LDL, VLDL, IgA, IgG, IgM, C3, C4, Hb, Hct and peripheral smear prior to induction and at the end of the anaesthesia for each application. Tissue samples were obtained after the last application of anaesthesia. Cholesterol levels obtained after second application, GGT and biluribin after third, C3 after fourth and C4 after fifth were found to be significantly elevated when compared with the control levels, however, the levels of IgG and IgM significantly decreased after the third application of anaesthesia. Histopathological examination revealed degenerative changes in livers and kidneys. Our study revealed that, repeated propofol anaesthesia can lead to hyperlipidemia, immunosuppression and degenerative changes in liver and kidney. Further studies are warranted in this subject.
Keywords: biochemistry; hematology; immunoglobulin; liver histopathology; propofol; renal histopathology; repeated anaesthesia